Sufism in the West - Malik, Jamal; Hinnells, John (Taylor & Francis, 2006)
With the increasing Muslim diaspora in post-modern Western societies, Sufism - intellectually as well as sociologically - may eventually become Islam itself due to its versatile potential. Although Sufism has always provoked considerable interest in the West, no volume has so far been written which discusses this aspect of Islam in terms of how it is practised in Western societies. Bringing together leading international authorities to survey the history of Islamic mysticism in North America and Europe, this book elaborates the ideas and institutions which organize Sufism and folk-religious practices. The chapters cover: the orders and movements their social base organization and institutionalization recruitment-patterns in new environments channels of disseminating ideas, such as ritual, charisma, and organization reasons for their popularity among certain social groups the nature of their affiliation with the countries of their origin. Providing a fascinating insight into how Sufism operates within different spheres of society, Sufism in the West is essential reading for students and academics with research interests in Islam, Islamic history and social anthropology.